2012
DOI: 10.1001/2012.jama.11132
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Adiposity and the Risk of Prediabetes and Type 2 Diabetes in Obese Adults

Abstract: MARKED INCREASE IN THEprevalence of overweight and obesity 1 has contributed to a doubling in type 2 diabetes mellitus incidence over the past 3 decades. 2 Increasing rates of diabetes among obese individuals has counterbalanced reductions in other cardiovascular disease (CVD) risk factors and is the primary factor contributing to a slowed decline in CVD event rates in the general population. 3 Prediabetes, an intermediate hyperglycemia phenotype and risk factor for diabetes, 4 is also associated with obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
430
6
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 548 publications
(482 citation statements)
references
References 41 publications
(51 reference statements)
24
430
6
9
Order By: Relevance
“…Furthermore, WC measures include both VAT and abdominal subcutaneous adipose tissue compartments, which are anatomically and physiologically distinct and are associated with a different cardiometabolic risk profile 42. Visceral fat, but not abdominal subcutaneous tissue, has been associated with type 2 diabetes mellitus,44 hypertension,45 and alterations in left ventricular structure and function 41. Moreover, when visceral fat was replaced with WC in a predictive model of type 2 diabetes mellitus, WC was not significantly associated with the outcome 44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, WC measures include both VAT and abdominal subcutaneous adipose tissue compartments, which are anatomically and physiologically distinct and are associated with a different cardiometabolic risk profile 42. Visceral fat, but not abdominal subcutaneous tissue, has been associated with type 2 diabetes mellitus,44 hypertension,45 and alterations in left ventricular structure and function 41. Moreover, when visceral fat was replaced with WC in a predictive model of type 2 diabetes mellitus, WC was not significantly associated with the outcome 44.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral fat, but not abdominal subcutaneous tissue, has been associated with type 2 diabetes mellitus,44 hypertension,45 and alterations in left ventricular structure and function 41. Moreover, when visceral fat was replaced with WC in a predictive model of type 2 diabetes mellitus, WC was not significantly associated with the outcome 44. In summary, although we did not find major differences between the effects of generalized versus central adiposity in this study, more detailed and precise imaging‐based assessments of adipose depots are required to further delineate the independent effects of varying depots on cardiac structure and function over time.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the participant selection process and the study design have been previously described (Neeland et al, 2012;Victor et al, 2004).…”
Section: Participants and Assessmentsmentioning
confidence: 99%
“…However, there is conflicting evidence that suggests excess visceral fat and insulin resistance, but not general adiposity are associated with incident pre-diabetes and type 2 diabetes in obese individuals 10 . A recent study of almost 30,000 individuals demonstrated that metabolically unhealthy obese individuals have a greater risk of developing diabetes than the metabolically healthy obese 11 .…”
Section: Introductionmentioning
confidence: 99%